Sprinting patterns of national rugby league competition - Gabbett, T. J. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to investigate the sprinting demands of National Rugby League (NRL) competition and characterize the sprinting patterns of different rugby league playing positions. Thirty-seven elite rugby league players (mean ± SE age: 23.6 ± 0.5 years) underwent global positioning satellite analysis during 104 NRL appearances. The majority (67.5%) of sprint efforts were across distances of <20 m. The most common sprint distance for hit-up forwards was 6-10 m (46.3%). Outside backs had a greater proportion (33.7%) of sprint efforts over distances of 21 m. The proportion of sprint efforts over 40 m or greater for hit-up forwards, wide running forwards, adjustables, and outside backs was 5.0, 7.4, 5.0, and 9.7%, respectively. Of the sprints performed, approximately 48.0% involved contact, approximately 58.0% were preceded by forward locomotion (forward walking, jogging, or striding), whereas over 24.0% occurred from a standing start. Hit-up forwards more commonly sprinted from a standing start, or after lateral movement, whereas forward striding activities more commonly preceded sprint efforts for the adjustables and outside backs. The majority of sprint efforts were performed without the ball (78.7 vs. 21.3%). Most sprint efforts (67.5%) were followed by a long recovery (i.e., 5 minutes). Outside backs had the greatest proportion (76.1%) of long duration recovery periods and the smallest proportion (1.8%) of short duration recovery periods (i.e., <60 seconds) between sprints. The results of this study demonstrate differences among rugby league playing positions for the nature of sprint efforts and the typical distances covered during these efforts. Furthermore, the activities preceding and the recovery periods after sprint efforts were different among playing positions. These findings suggest that rugby league sprint training should be tailored to meet the individual demands of specific playing positions.